Genetic Variation for Harvest Index in Upland Cotton (G. Hirsutum L.) - PALVE, S. M.; WAGHMARE, V. N.; KATE, N. (Cotton Research Journal, 2021)
Harvest index describes plant capacity to allocate biomass (assimilates) to reproductive parts. The harvest index is an important trait for cotton breeding programme especially under rainfed conditions. Efforts were made at ICAR–CICR, Nagpur, India for developing breeding lines of upland cotton for improved plant type and better fibre properties. During the year 2016-17 an experiment was conducted comprising 14 advanced breeding lines (F8 generation) along with four released varieties for evaluation of yield and yield components and fibre properties under rainfed conditions at 150 days after sowing (DAS). Amongst the breeding lines, CNH 09-9 and CNH 09-77 recorded highest harvest index (HI) of 0.6 compared to CNH 09-78 and CNH 712-13 which recorded harvest index of 0.2 and 0.3, respectively. Breeding lines CNH 10-6-1, CNH 12-12-4 and CNH 12-4-2 recorded harvest index of 0.3 which had plant height of 127.8, 111.6 cm and 103.8 cm, respectively. The released variety LRK 516 had recorded HI of 0.6 followed by NH 615, LRA 5166 and Suraj with HI of 0.5 indicating the importance of plant architecture while selecting plant type for improving yield per plant under rainfed situations. The varieties LRK 516, NH 615, LRA 5166 and Suraj had recorded plant height of 64.3 cm, 89.9 cm, 87.4 cm, and 81.3 cm, respectively. Breeding lines CNH 09-4 and CNH 09-7 recorded harvest index of 0.5 and plant height of 71.7 and 65.7 cm, respectively. Plant height had significant genotypic and phenotypic positive correlations (r = 0.52, r = 0.55) with number of sympodia and significant negative correlation (r = - 0.61, r = - 0.55) with harvest index. Boll number per plant had significant positive correlations (r=0.47) at genotypic level with seed cotton yield. Harvest index had significant positive genetic and phenotypic correlation(r=0.66, r=0.61) with seed cotton yield. Thus, selection of relatively determinate and fully indeterminate parents in breeding programme would generate large extent of variability for plant type and harvest index which would provide opportunity to select desirable compact plant type with high harvest index and productivity under rainfed situations.